Research on the anti-duodenal ulcer effect of Vien Khoi Tim capsules on Wistar rats with duodenal ulcers caused by cysteamine - Nguyen, Thị Minh Thu; Pham, Thi Van Anh; Nguyen, Thi Ha; Nguyen, Thi Loan (Tạp chí Y Dược cổ truyền Việt Nam, 2024)
Objective: To evaluate the anti-duodenal ulcer effect of Vien Khoi Tim capsules on Wistar rats. Subjects and methods: The duodenal ulcer model in rats receiving cysteamine (CYS) orally at a dose regimen of 400 mg/kg/time × 2 times were applied. Rats were divided into 5 groups comprising 12 rats each. In which, the biological proof group only received distilled water while the others were given distilled water, test samples (237.6 or 712.8 mg/kg/day) or famotidine continuously for 10 days before being taken CYS. After 24 hours of treatments, all rats were anesthetized with chloral hydrate before being dissected and observing their duodenums to evaluate the results. Results: Vien Khoi Tim remarkably reduced rats’ ulcer indices compared to those of the model group (p < 0.05) with ulcer inhibition rates of 58.5% and 53.7%, respectively. No ulcer lesions or apoptosis were detected in the duodenal microscopic samples of both groups being taken Vien Khoi Tim, while the model group had both ulcer lesions and apoptosis at the rate of 33.33%. Conclusion: Vien Khoi Tim hard capsules were highly effective against duodenal ulcers in rats at oral dose regimens of 237.6 and 712.8 mg/kg/day × 10 consecutive days.